TINGKAT KEMATANGAN BIJI KOPI ARABICA (Coffea arabica L.) DALAM MENGHASILKAN KADAR KAFEIN - Srikandi Srikandi; Aprilia Widia Kristanti; RTM Sutamihardja (Universitas Nusa Bangsa, 2019)
Levels of Arabica (Coffea Arabica L.) Coffee Materials in Producing CaffeinÂ Coffee is a plantation crop that has long been cultivated in Indonesia. One type of coffee grown in Indonesia, namely arabica coffee. Arabica coffee is coffee that has superior quality compared to other types of coffee. Testing of caffeine content in Sukamakmur village arabica coffee is differentiated into three types of coffee berries based on the maturity level of the coffee fruit. The level of maturity of coffee fruit is marked by the color of coffee fruit skin. The collection of young coffee fruit is characterized by green fruit rind, half-aged coffee, orange rind and old coffee, dark red rind. Arabica coffee fruit is processed from drying, drying, and roasting and grinding into arabica ground coffee. Powder coffee samples are used for water content testing, phytochemical identification, and caffeine level testing. Caffeine content testing using UV-Vis spectrophotometry. The results of water content testing showed that the highest water content was found in coffee with a maturity level of half old, the lowest moisture content found in old coffee. Phytochemical identification testing performed showed powdered coffee samples containing active compounds of saponins, flavonoids, and alkaloids, as well as tannins. The highest caffeine content is found in ground coffee with the maturity level of coffee half old at 1.56% and the lowest caffeine level in ground coffee with a young coffee level of 0.93%.Keywords : Coffea arabica L., Level of maturity, Level of caffeine.Â ABSTRAKKopi adalah tanaman perkebunan yang sudah lama dibudidayakan di Indonesia. Salah satu jenis kopi yang ditanam di Indonesia, yaitu kopi arabika. Kopi arabika merupakan kopi yang memiliki kualitas superior dibanding jenis kopi lainnya. Pengujian kadar kafein pada kopi arabika desa Sukamakmur dibedakan menjadi tiga jenis pengambilan buah kopi berdasarkan tingkat kematangan buah kopi. Tingkat kematangan buah kopi ditandai dengan warna kulit buah kopi. Pengambilan buah kopi muda ditandai dengan kulit buah berwarna hijau, kopi setengah tua, kulit buah berwarna jingga dan kopi tua, kulit buah berwarna merah tua. Buah kopi arabika diolah dari penjemuran, pengeringan, dan penyangraian serta penggilingan menjadi kopi bubuk arabika. Sampel kopi bubuk digunakan untuk bahan pengujian kadar air, identifikasi fitokimia dan pengujian kadar kafein. Pengujian kadar kafein menggunakan metode spektrofometri UV-Vis. Hasil pegujian kadar air menunjukkan bahwa kadar air tertinggi terdapat pada kopi dengan tingkat kematangan setengah tua, kadar air terendah terdapat pada kopi tua. Pengujian identifikasi fitokimia yang dilakukan menunjukan sampel kopi bubuk mengandung senyawa aktif saponin, flavonoid, dan alkaloid, serta tanin. Kadar kafein tertinggi terdapat pada kopi bubuk dengan tingkat kematangan kopi setengah tua sebesar 1,56% dan kadar kafein terendah pada kopi bubuk dengan tingkat kopi muda sebesar 0,93%.Kata kunci: Coffea arabica L., Tingkat kematangan, Kadar kafein.